Energy Improvement in urban domestic & tertiary sector of Buenos Aires - Rosenfeld, Elías (1989)
The proyect disclosed how power is used in the AMBA (Buenos Aires Metropolitan Area) residential area, which includes the most important metropolitan sector in the Republic of Argentina.